Emotional activation during teaching situations in science teachers education - Forero Díaz, Sandra Milena; Castro Castillo, Diana Carolina; Callejas Arevalo, Ronal Enrique (Frontiers in Education, 2026)
Research on emotions in science education has gained increasing relevance in recent years, as it is now recognized that participants in the educational process, regularly experience emotions in the classroom, which in turn impact both teaching and learning. Teachers are responsible not only for promoting students’ academic achievement but also for promoting their holistic personal development. Consequently, addressing the affective dimension from the outset of science teacher education is essential in order to cultivate professional competencies that support emotionally informed teaching practices. This mixed-methods study involved 125 students from the Faculty of Science and Technology at the Universidad Pedagógica Nacional, Colombia. It examined emotions experienced in two different teaching situations: experimental or practical activities and lecture-based explanations. Findings indicate that emotional activation and self-efficacy in these situations are dynamic processes mediated by context, prior experience, perceived control, and the value attributed to the task. Understanding these affective experiences highlights the importance of strengthening initial science teacher education to equip future science teachers with the tools needed to address the emotional demands of teaching practice.